Pathogenic synergism between Treponema hyodysenteriae and other selected anaerobes in gnotobiotic pigs. - Whipp, S C (1979)
Gnotobiotic pigs were orally exposed to various anaerobes at 6 to 9 days of age and similarly inoculated with Treponema hyodysenteriae B204 3 to 6 days later. Watery diarrhea and fecal excretion of large quantities of mucus and some fibrin clots were observed 4 to 20 days after inoculation with B204 if other anaerobes were present. Colonic lesions characteristic of swine dysentery were observed when B204 was present with Fusobacterium necrophorum, three strains of Bacteroides vulgatus, a Clostridium species, and Listeria denitrificans individually and when some of these microbes were present in various combinations, but not when B204 was present alone. These results are consistent with the conclusion that T. hyodysenteriae is the primary pathogen in the etiology of swine dysentery and that the presence of one or more other anaerobes is a prerequisite for expression of pathogenicity of T. hyodysenteriae. This prerequisite can be met by a variety of anaerobes.